The Influence of Return on Assets (ROA), Total Assets Turnover (TATO), Debt to Equity Ratio (DER), and Earnings per Share (EPS) on Stock Returns: A Case Study of the Oil and Gas Industry Listed on the Indonesia Stock Exchange for the 2019–2023 Period - Muhammad Rasyid Ridho Abdullah; Dwi Urip Wardoyo (LP2M IAIN Palopo, 2025)
One of the main considerations for investors in the capital market is obtaining an optimal stock return, as stock returns reflect market perceptions of a company’s performance and future prospects. This study aims to examine how Return on Assets (ROA), Total Assets Turnover (TATO), Debt to Equity Ratio (DER), and Earnings per Share (EPS) influence stock returns in oil and gas companies listed on the Indonesia Stock Exchange during the 2019–2023 period. A quantitative method with a descriptive approach was applied. The research population consisted of oil and gas companies registered on the exchange within the specified period. Using a purposive sampling technique, 16 companies met the criteria, producing a total of 80 observational data points. Data analysis was conducted using panel data regression through EViews 12. The findings indicate that ROA, TATO, DER, and EPS jointly have a significant effect on stock returns. However, in the partial analysis, only ROA demonstrates a positive and significant influence on stock returns, while TATO, DER, and EPS do not show significant effects. These results highlight that profitability, as represented by ROA, plays a more dominant role in determining stock return movements in the oil and gas sector